Ethics, Morals, and Morality: Between Anonymity and Responsibility - Najwa Aidila Fitri; Faqih Hanan Zaidan; Lola Suci Mayrani; Juni Wahyu (ISNU Nine-Star Multidisciplinary Journal, 2025)
Anonymity in the digital space has blurred the boundaries between freedom of expression and moral responsibility. This paper examines how anonymity impacts ethical, moral, and ethical practices in digital life, particularly from the perspective of Islamic values. This research uses a qualitative literature review method. Based on literature from Indonesian scientific journals, it was found that neglect of responsibility is often triggered by the perception that anonymity frees individuals from social oversight. However, Islamic moral and ethical values emphasize the importance of inner awareness in acting, even without external oversight. Therefore, anonymity should not be a reason for the decline of ethics, but rather a challenge to strengthen internal moral values as the primary moral compass. Thus, this paper emphasizes the importance of strengthening individual ethics based on morality in facing the reality of anonymous digital communication.